Teachers’ Diagnostic Game Playing Compe¬tence (Criteria «Game Playing Knowledge») - Gordienko-Mytrofanova, I. (Psychological Prospects Journal, 2013)
The article deals with the description of game playing knowledge test. It is a test that focuses on the teaching knowledge needed by teachers of primary and secondary school who actively applies didactic games and manipulative games in particular in his teaching practice. They are subject, personality, procedural, and value-semantic knowledge. The groups of knowledge are defined from the position of the competence approach.